A ternary doped titanium anode for PCB copper electroplating and a preparation method and application thereof
Patent Information
- Application Number
- CN202611207912.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-08-11
AI Technical Summary
[0003]目前 PCB 电镀铜工序主要采用两类阳极:一类为可溶性磷铜阳极,通过自身溶解补充镀液铜离子,但存在易产生阳极泥、需频繁停机补料、电流分布均匀性差等缺陷,难以适配高电流密度与脉冲电镀工艺;另一类为不溶性钛阳极,自身不参与溶解反应,可维持镀液铜离子浓度稳定,配合含Fe²+/Fe³+氧化还原电对的酸性硫酸铜镀液体系,可大幅降低析氧副反应对有机添加剂的破坏,已成为高端 PCB 电镀产线的主流选型
通过Sn/Si/Mn三元微量共掺杂改性铱钽基电催化活性涂层,调控涂层表面电子结构与反应吸附能,在含Fe²+/Fe³+氧化还原电对的酸性硫酸铜镀液体系中,可显著提升Fe²+氧化主反应的催化选择性,有效抑制高电流密度工况下的析氧副反应,减少强氧化性中间产物对镀液中有机光亮剂、整平剂的氧化破坏,降低添加剂消耗量,维持镀层平整度与致密性,保障 PCB 电镀铜的镀层质量稳定。
Smart Images

Figure CN122707118B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of printed circuit board manufacturing technology, and in particular to a ternary doped titanium anode for PCB copper electroplating, its preparation method and application. Background Technology
[0002] In printed circuit board (PCB) manufacturing, copper electroplating is a core process for achieving hole metallization and line thickening. The performance of the anode material directly determines the plating quality, production efficiency, and operating costs. As PCB products develop towards high precision and fine lines, production lines are gradually upgrading towards high current density and continuous production, placing higher demands on the catalytic selectivity, stability, and service life of the anode material.
[0003] Currently, the copper plating process for PCBs mainly uses two types of anodes: one is soluble phosphorus copper anodes, which replenish copper ions in the plating solution by dissolving themselves. However, they have drawbacks such as easy generation of anode sludge, frequent shutdowns for replenishment, and poor current distribution uniformity, making them unsuitable for high current density and pulse plating processes. The other type is insoluble titanium anodes, which do not participate in the dissolution reaction and can maintain a stable copper ion concentration in the plating solution. Combined with Fe²⁺... + / Fe³ + The acidic copper sulfate plating solution system with redox couples can significantly reduce the damage to organic additives caused by oxygen evolution side reactions, and has become the mainstream choice for high-end PCB electroplating production lines.
[0004] Existing commercially available insoluble titanium anodes mostly use IrO2-Ta2O5 composite oxide coatings. Although they have good electrochemical stability, they still have significant shortcomings under high current density conditions: First, the oxygen evolution side reaction of the coating is aggravated, and the generated strong oxidizing intermediate products will accelerate the decomposition of brighteners and leveling agents in the plating solution, resulting in high additive consumption, increased production costs, and fluctuations in coating quality. Second, after repeated pyrolysis and sintering, the coating is prone to developing through-cracks. Corrosive electrolytes penetrate and erode the titanium substrate along the cracks, causing the coating to peel off and fail, shortening the anode's service life, and failing to meet the requirements of long-term continuous operation of production lines.
[0005] To address the aforementioned issues, the industry commonly employs elemental doping to modify iridium-tantalum coatings. However, existing doping schemes primarily aim to enhance oxygen evolution catalytic activity, adapting to scenarios such as electrolytic hydrogen production and wastewater treatment. This technological orientation completely contradicts the requirements of PCB electroplating systems to suppress oxygen evolution and ensure the selectivity of the main reaction. Furthermore, existing modifications are mostly single-element or dual-element doping, making it difficult to simultaneously achieve multiple effects such as oxygen evolution potential control, coating microstructure densification, and improved thermal stability. There is a lack of dedicated modified anode solutions that can be directly adapted to the high current density copper electroplating conditions of PCBs. Summary of the Invention
[0006] The main objective of this invention is to provide a ternary doped titanium anode for copper electroplating on PCBs, its preparation method, and its application. This invention optimizes the electrocatalytic performance of the coating through synergistic optimization of ternary micro-co-doping, particularly in Fe²⁺-containing substrates. + / Fe³ + In acidic copper sulfate plating solutions, the redox couple can selectively suppress oxygen evolution side reactions, reduce organic additive losses, and extend anode service life, thus meeting the needs of high current density PCB copper plating production.
[0007] To achieve the above objectives, the present invention provides a method for preparing a ternary doped titanium anode for copper plating on PCBs, comprising the following steps: The titanium substrate was subjected to sandblasting roughening, annealing shaping and acid etching activation treatment in sequence to remove the oxide layer on the surface of the titanium substrate and form a uniform rough interface. After being rinsed with deionized water and dried, it was ready for use. A coating solution is prepared by dissolving chloroiridic acid, tantalum pentachloride, tin tetrachloride, tetraethyl orthosilicate, and manganese nitrate in anhydrous ethanol, wherein the molar ratio of iridium to tantalum is 6-8:2-4, and the molar amount of tin is 5-10 parts, the molar amount of silicon is 1-3 parts, and the molar amount of manganese is 0.5-2 parts, based on 1000 parts of iridium. The coating liquid is applied to the surface of the pretreated titanium substrate, dried at 50-100°C for 5-10 minutes, and then sintered at 350-550°C for 15-30 minutes. The coating, drying and sintering steps are repeated 8-15 times. The titanium substrate that has undergone repeated brushing and sintering is then subjected to a final heat treatment at 500–600℃ for 1–2 hours to obtain a material suitable for Fe²⁺-containing substrates. + / Fe³ + Insoluble ternary doped titanium anode for copper plating on PCBs using a redox couple system.
[0008] Furthermore, the amount of coating liquid used in a single application to the titanium substrate surface is 10-20 ml per square meter.
[0009] Furthermore, during sintering, the temperature is increased to the sintering temperature at a rate of 5–10 °C / min, followed by isothermal sintering.
[0010] Furthermore, the total molar concentration of iridium, tantalum, tin, silicon, and manganese in the coating solution is 0.2–0.3 mol / L.
[0011] Furthermore, the sandblasting roughening uses 80-120 mesh white corundum sand, and the sandblasting pressure is 0.4-0.6 MPa.
[0012] Furthermore, the annealing and setting temperature is 500-600℃, and the holding time is 1-2 hours.
[0013] Furthermore, the acid etching activation treatment uses a 10-20% oxalic acid solution and is immersed at 80-90°C for 1-2 hours.
[0014] The present invention also provides a ternary doped titanium anode for copper plating of PCBs, which is prepared by the above-described preparation method for ternary doped titanium anodes for copper plating of PCBs.
[0015] Furthermore, ternary doped titanium anodes for PCB copper plating include: Titanium matrix; An iridium-tantalum-based electrocatalytic active coating is formed on the surface of the titanium substrate, wherein the molar ratio of iridium to tantalum in the iridium-tantalum-based electrocatalytic active coating is 6-8:2-4, and the molar amount of tin is 5-10 parts, the molar amount of silicon is 1-3 parts, and the molar amount of manganese is 0.5-2 parts, based on 1000 parts of iridium. The ternary doped titanium anode is in the Fe²⁺ content + / Fe³ + It is used as an insoluble anode in acidic copper sulfate plating solutions containing redox couples.
[0016] This invention also provides an application of a ternary doped titanium anode for copper plating on PCBs, wherein the aforementioned ternary doped titanium anode for copper plating on PCBs is applied to Fe²⁺-containing... + / Fe³ + In an acidic copper sulfate plating solution system with a redox couple, it is used as an insoluble anode for copper electroplating.
[0017] The method for preparing a ternary doped titanium anode for PCB copper electroplating provided in this invention has the following beneficial effects: By modifying an iridium-tantalum-based electrocatalytic active coating with Sn / Si / Mn ternary micro-co-doping, the electronic structure and reaction adsorption energy of the coating surface were controlled, and the coating was used in Fe²⁺-containing... + / Fe³ + In acidic copper sulfate plating solutions with redox couples, Fe²⁺ can be significantly increased. + The catalytic selectivity of the main oxidation reaction effectively suppresses the oxygen evolution side reaction under high current density conditions, reduces the oxidative damage of strong oxidizing intermediates to organic brighteners and leveling agents in the plating solution, reduces additive consumption, maintains the smoothness and density of the plating layer, and ensures the stability of the plating quality of copper electroplating on PCBs.
[0018] The three doping elements play a synergistic role in the pyrolysis sintering process of the coating. They can refine the oxide grains, fill the microcracks and pores inside the coating, improve the overall density of the coating and its bonding strength with the titanium substrate, prevent acidic electrolyte from penetrating into the substrate along the defects, alleviate the problems of coating peeling and titanium substrate passivation failure, significantly extend the continuous service life of the anode, reduce the frequency of production line downtime for replacement, and reduce production and maintenance costs.
[0019] By employing micro-doping at the thousand-level, the catalytic performance and structural stability of the coating can be comprehensively improved without increasing the proportion of the precious metal iridium to enhance the anode performance. This effectively controls the anode preparation cost and is suitable for the application needs of large-scale production lines such as vertical continuous electroplating and horizontal copper plating of PCBs, thus possessing good industrialization and promotion value. Attached Figure Description
[0020] Figure 1 This is a flowchart of a method for preparing a ternary doped titanium anode for copper electroplating of PCBs, provided in an embodiment of the present invention; Figure 2 This is a comparison table of anodic oxygen evolution potentials in the PCB acid copper plating system of this invention; Figure 3 This is a test data table of the consumption of organic additives in the electroplating solution in this invention; Figure 4 This is a table showing the anodic durability of the acidic copper sulfate plating solution system in this invention; Figure 5 This is a diagram of the oxygen evolution potential of the comparative example and embodiment in this invention; Figure 6 This is a SEM image of Embodiment 1 in this invention; Figure 7 This is the SEM image of Comparative Example 1 in this invention; Figure 8 This is the SEM image of Comparative Example 3 in this invention; The realization of the objective, functional features and advantages of the present invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation
[0021] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0022] Reference Figure 1 This is a schematic flowchart of a method for preparing a ternary doped titanium anode for copper plating on PCBs, as proposed in this invention, including the following steps: S1. The titanium substrate is subjected to sandblasting roughening, annealing shaping and acid etching activation treatment in sequence to remove the oxide layer on the surface of the titanium substrate and form a uniform rough interface. After being rinsed with deionized water and dried, it is ready for use. S2, a coating solution is prepared by dissolving chloroiridic acid, tantalum pentachloride, tin tetrachloride, tetraethyl orthosilicate and manganese nitrate in anhydrous ethanol, wherein the molar ratio of iridium to tantalum is 6-8:2-4, and based on 1000 parts of iridium, the molar amount of tin is 5-10 parts, the molar amount of silicon is 1-3 parts, and the molar amount of manganese is 0.5-2 parts. S3, the coating liquid is applied to the surface of the pretreated titanium substrate, dried at 50-100°C for 5-10 minutes, and then sintered at 350-550°C for 15-30 minutes. The coating, drying and sintering steps are repeated 8-15 times. S4. The titanium substrate that has undergone repeated brushing and sintering is subjected to a final heat treatment at 500–600°C for 1–2 hours to obtain a material suitable for Fe²⁺-containing titanium substrates. + / Fe³ + Insoluble ternary doped titanium anode for copper plating on PCBs using a redox couple system.
[0023] As described in step S1 above, the titanium substrate is selected from industrial pure titanium plates or meshes. It is roughened by sandblasting with white corundum abrasive, with the abrasive particle size controlled at 80–120 mesh and the sandblasting pressure maintained at 0.4–0.6 MPa. The abrasive particles uniformly impact the substrate surface, removing surface processing marks and the original oxide film, while simultaneously forming a uniformly distributed uneven morphology, improving surface roughness and providing a reliable mechanical bonding foundation for coating adhesion. After sandblasting, the titanium substrate is sent to a muffle furnace for annealing and shaping. The furnace temperature is raised to 500–600℃ and held at that temperature for 1–2 hours, followed by slow cooling with the furnace. High-temperature treatment can eliminate internal residual stress introduced during the sandblasting process, stabilize the substrate geometry, avoid deformation and warping during high-temperature sintering, and simultaneously make the surface titanium atom arrangement more regular, improving interfacial bonding stability. After annealing, the substrate is immersed in an oxalic acid solution for acid etching activation, with the solution mass fraction controlled at 10–20%, the system temperature maintained at 80–90℃, and the immersion time at 1–2 hours. In an acidic environment, micro-dissolution occurs on the surface of the titanium substrate, completely removing the original thin oxide layer and forming fine and uniform corrosion pits, further increasing the effective contact area of the surface. After treatment, the substrate is removed, repeatedly rinsed with deionized water until the surface is neutral, dried in an oven, and then stored in a dry environment for later use.
[0024] As described in step S2 above, five precursor raw materials—iridium chloroacetic acid, tantalum pentachloride, tin tetrachloride, tetraethyl orthosilicate, and manganese nitrate—are weighed according to a preset component ratio and added sequentially to anhydrous ethanol solvent. The molar ratio of iridium to tantalum is controlled at 6–8:2–4. Based on 1000 molar parts of iridium, the amounts of the three doping elements—tin, silicon, and manganese—introduced are 5–10 parts, 1–3 parts, and 0.5–2 parts, respectively, modifying the iridium-tantalum main coating through trace doping without damaging the basic structure of the original oxide framework. The mixture is continuously magnetically stirred at room temperature for 2–4 hours. During stirring, the metal precursors gradually dissociate and disperse, and the solute molecules are uniformly distributed in the ethanol solvent. The system gradually transitions from turbid to clear and transparent, without precipitation or stratification, forming a uniform and stable coating precursor solution. The total amount of anhydrous ethanol added is adjusted to maintain the total molar concentration of the five metal elements in the coating solution at 0.2–0.3 mol / L. This concentration range ensures a uniform and moderate coating load during a single application, preventing both excessively high concentrations that could lead to coating buildup and cracking, and excessively low concentrations that could result in multiple applications failing to achieve the target thickness, thus guaranteeing the uniformity of the coating structure and the consistency of its performance after pyrolysis sintering.
[0025] As described in step S3 above, the prepared coating solution is uniformly applied to the pretreated titanium substrate surface. The amount applied per square meter of substrate surface per coat is controlled at 10 to 20 ml to ensure a thin and uniform film without accumulation or dripping. After coating, the substrate is allowed to stand at room temperature for a short time to allow the coating solution to fully spread and wet the rough interface. Then, it is placed in an oven at 50 to 100°C and kept at that temperature for 5 to 10 minutes to allow the ethanol solvent to evaporate slowly and the solute to be uniformly deposited on the substrate surface, forming a dense precursor film. The dried substrate is then transferred to a muffle furnace for pyrolysis sintering, with the temperature increased to 350 to 550°C at a rate of 5 to 10°C per minute and held at that temperature for 15 to 30 minutes. Under high temperature conditions, the metal precursor undergoes a thermal decomposition reaction, gradually transforming into a composite oxide crystalline phase, while simultaneously forming a strong bonding interface with the titanium substrate surface. After each sintering cycle, the substrate is removed and allowed to cool naturally to room temperature. The coating, drying, and sintering processes are repeated, and the entire cycle is repeated 8 to 15 times. The layered coating structure is dense and uniform, and the thickness gradually accumulates with the number of cycles, avoiding the cracking and peeling problem caused by excessive film thickness in a single cycle, and finally forming an iridium-tantalum-based active coating that has both catalytic activity and structural stability.
[0026] As described in step S4 above, the titanium substrate, after completing all coating and sintering cycles, is sent back to the muffle furnace for final heat treatment. The furnace temperature is steadily raised to 500-600℃ and maintained for 1-2 hours to allow the multi-layered coating crystal phases to grow and mature further, ensuring full fusion and diffusion at the interfaces of each layer. This eliminates residual internal stress from layer-by-layer sintering and reduces microporosity and microcrack defects within the coating. The high-temperature environment also promotes the uniform distribution of doping elements in the oxide lattice, allowing the modifying effects of tin, silicon, and manganese to be fully realized, stabilizing the electronic structure and interface energy states of the coating, and enhancing catalytic selectivity and structural stability. After heat treatment, the substrate is slowly cooled to room temperature with the furnace to avoid thermal stress shock caused by rapid cooling, ensuring that the bonding strength between the coating and the substrate is not damaged. The resulting ternary doped titanium anode has a dense and uniform structure, with a strong bond between the coating and the substrate. It can be directly adapted to acidic copper sulfate plating solutions containing ferrous and ferric redox couples, serving as an insoluble anode in PCB copper plating processes, meeting the requirements for long-term stable operation under high current density.
[0027] The present invention will be specifically described below through examples.
[0028] Example 1 The titanium substrate is made of industrial pure titanium TA2 titanium mesh, which is roughened by sandblasting with 100-mesh white corundum abrasive at a pressure controlled at 0.5 MPa. The abrasive particles uniformly impact the substrate surface, removing surface machining marks and the original oxide film, forming a rough interface with an orderly texture, providing mechanical bonding conditions for coating adhesion. After sandblasting, the titanium substrate is placed in a muffle furnace for annealing and shaping. The furnace temperature is raised to 550℃ and held at that temperature for 1.5 hours, followed by slow cooling with the furnace. This high-temperature treatment eliminates internal residual stress introduced during sandblasting, stabilizes the substrate geometry, and prevents deformation and warping during high-temperature sintering. After annealing, the substrate is immersed in a 15% oxalic acid solution for acid etching activation, with the system temperature maintained at 85℃ for 1.5 hours. In an acidic environment, micro-dissolution occurs on the surface of the titanium substrate, the thin oxide layer is completely removed, and fine and uniform corrosion pits are formed, further increasing the effective contact area of the surface. After the treatment is completed, the substrate is taken out, rinsed repeatedly with deionized water until the surface is neutral, and then placed in an oven to dry and stored in a dry environment for later use.
[0029] Five precursor materials—iridium chloroacetic acid, tantalum pentachloride, tin tetrachloride, tetraethyl orthosilicate, and manganese nitrate—weighed according to the set component ratio and added sequentially to anhydrous ethanol solvent. The molar ratio of iridium to tantalum was controlled at 7:3. Based on 1000 molar parts of iridium, the amounts of tin, silicon, and manganese dopants introduced were 7 parts, 1 part, and 2 parts, respectively. The total amount of anhydrous ethanol added was adjusted to achieve a total molar concentration of 0.25 mol / L for the five metal elements in the coating solution. The mixture was continuously magnetically stirred at room temperature for 3 hours. The metal precursors gradually dissociated and dispersed, and the system gradually transitioned to a clear and transparent state, forming a homogeneous and stable coating precursor solution.
[0030] The prepared coating solution was evenly applied to the pretreated titanium substrate surface. After application, the substrate was left to stand at room temperature for 8 minutes to allow the coating solution to fully spread and wet the rough interface. Then, it was placed in a 90°C oven for 8 minutes to allow the ethanol solvent to slowly evaporate and the solute to be evenly deposited on the substrate surface to form a precursor film.
[0031] The dried matrix was then transferred to a muffle furnace for pyrolysis sintering, with the temperature increased to 400°C at a rate of 8°C per minute and held at that temperature for 25 minutes. Under high-temperature conditions, the metal precursor underwent thermal decomposition, gradually transforming into a composite oxide crystalline phase, while simultaneously forming a strong bonding interface with the titanium matrix surface.
[0032] After a single sintering cycle, the substrate is removed and allowed to cool naturally to room temperature. The coating, drying, and sintering processes are repeated, with the entire cycle repeated 10 times. The layer-by-layer coating structure is dense and uniform, with the thickness gradually accumulating with each cycle, avoiding cracking and peeling caused by excessive thickness in a single coating. The titanium substrate, having completed all coating and sintering cycles, is then placed back into a muffle furnace for final heat treatment. The furnace temperature is steadily raised to 550°C and held constant for 1 hour, allowing the multi-layered coating crystal phases to grow and mature further, ensuring full fusion and diffusion at the interfaces of each layer, eliminating residual internal stress from layer-by-layer sintering, and promoting uniform distribution of dopant elements within the oxide lattice. After heat treatment, the substrate is slowly cooled to room temperature with the furnace, ultimately yielding the ternary doped titanium anode product.
[0033] The electrochemical performance, service stability, and microstructure of the prepared anode samples were comprehensively characterized, and the test results corresponded to... Figures 2 to 8 .
[0034] Oxygen evolution potential (OEP) testing was conducted in a simulated acidic plating bath environment to determine the selectivity of the catalytic reaction at the anode. Figure 2 The oxygen evolution potential values of each group of samples are summarized in tabular form. Figure 5The differences are visually presented in the form of a bar chart. The oxygen evolution potential (OE) of the ternary doped anode prepared in this embodiment reaches 1.56V, which is 110mV higher than that of the undoped Comparative Example 1, and also significantly higher than the single-doped and double-doped comparative samples. The increased OE potential means that the threshold for the OE side reaction is raised, allowing the anode to preferentially catalyze the main reaction of ferrous iron to ferric iron, effectively reducing the negative impact of the side reaction on the plating bath system.
[0035] Figure 3 This paper presents comparative data on the consumption of organic additives in electroplating solutions corresponding to different doping systems. In this example, the consumption of brightener decreased by 25%, and the consumption of leveling agent decreased by 20%, which is better than that of the single-doped and double-doped systems. The reduction in additive consumption is directly due to the suppression of the oxygen evolution side reaction, the reduction in the formation of strongly oxidizing intermediates, and the weakening of the oxidative damage to brighteners and leveling agents. This maintains the long-term stability of the plating solution composition and reduces the cost of auxiliary materials in the production process.
[0036] Figure 4 The results of the anodic durability test under the acidic copper sulfate plating solution system show that the accelerated hardening life of the sample in this embodiment can reach 712 hours, which is more than 60% higher than that of Comparative Example 1. The life improvement is due to the optimization of the coating structure. The dense and continuous oxide layer can prevent the corrosive electrolyte from penetrating into the substrate, delay the passivation of the substrate and the peeling of the coating, and support the long-term continuous operation of the electroplating production line.
[0037] Microscopic morphology characterization results correspond Figure 6 , Figure 6 In this embodiment, the surface cracks of the ternary doped coating are almost completely eliminated, exhibiting a continuous and dense morphology with only extremely fine surface textures. The progressive changes in the microstructure directly demonstrate the inhibitory effect of ternary doping on thermal stress cracking of the coating, and also provide a structural explanation for the significant improvement in anode service life.
[0038] Example 2 The titanium substrate is made of industrial pure titanium TA2 mesh, roughened by sandblasting with 100-mesh white corundum abrasive at a pressure controlled at 0.5 MPa. The abrasive particles uniformly impact the substrate surface, removing surface machining marks and the original oxide film, forming a rough interface with orderly contours, providing mechanical bonding conditions for coating adhesion. After sandblasting, the titanium substrate is annealed in a muffle furnace for shaping. The furnace temperature is raised to 550℃ and held at that temperature for 1.5 hours, followed by slow cooling with the furnace. This high-temperature treatment eliminates internal residual stress introduced during sandblasting, stabilizes the substrate geometry, and prevents deformation and warping during high-temperature sintering. The annealed substrate is then immersed in a 15% oxalic acid solution for acid etching activation, with the system temperature maintained at 85℃ for 1.5 hours. Under acidic conditions, micro-dissolution occurs on the titanium substrate surface, completely removing the thin oxide layer and forming fine, uniform corrosion pits, further increasing the effective surface contact area. After processing, remove the substrate, rinse it repeatedly with deionized water until the surface is neutral, dry it in an oven, and then store it in a dry environment for later use.
[0039] Five precursor materials—iridium chloroacetic acid, tantalum pentachloride, tin tetrachloride, tetraethyl orthosilicate, and manganese nitrate—were weighed according to the set component ratio and added sequentially to anhydrous ethanol solvent. The molar ratio of iridium to tantalum was controlled at 7:3. Based on 1000 molar parts of iridium, the amounts of tin, silicon, and manganese dopants introduced were 7 parts, 2 parts, and 1 part, respectively. The total amount of anhydrous ethanol added was adjusted to achieve a total molar concentration of 0.25 mol / L for the five metal elements in the coating solution. The mixture was continuously magnetically stirred at room temperature for 3 hours, allowing the metal precursors to gradually dissociate and disperse, and the system to gradually transition to a clear and transparent state, forming a uniform and stable coating precursor solution. The prepared coating solution was uniformly brushed onto the pretreated titanium substrate surface. After brushing, the mixture was allowed to stand at room temperature for 5 minutes to allow the coating solution to fully spread and wet the rough interface. Then, it was placed in a 100°C oven for 5 minutes to allow the ethanol solvent to slowly evaporate, and the solute to be uniformly deposited on the substrate surface to form a precursor film.
[0040] The dried substrate is transferred to a muffle furnace for pyrolysis sintering, with the temperature increased to 550°C at a rate of 8°C per minute and held at that temperature for 15 minutes. Under high-temperature conditions, the metal precursor undergoes thermal decomposition, gradually transforming into a composite oxide crystalline phase, while simultaneously forming a strong bonding interface with the titanium substrate surface. After each sintering cycle, the substrate is removed and allowed to cool naturally to room temperature. The coating, drying, and sintering process is repeated 10 times. The layer-by-layer stacked coating structure is dense and uniform, with the thickness gradually accumulating with each cycle, avoiding cracking and peeling caused by excessive thickness in a single coating. The titanium substrate, after completing all coating and sintering cycles, is then returned to the muffle furnace for final heat treatment. The furnace temperature is steadily raised to 550°C and held for 1 hour, allowing the multi-layer stacked coating crystalline phase to grow and mature further, ensuring full fusion and diffusion at each layer interface, eliminating residual internal stress from layer-by-layer sintering, and promoting uniform distribution of dopant elements within the oxide lattice. After heat treatment, the substrate is slowly cooled to room temperature with the furnace, ultimately yielding the ternary doped titanium anode product.
[0041] The electrochemical performance and service stability of the prepared anode samples were characterized, and the test results can be correlated with... Figures 2 to 5 .
[0042] The oxygen evolution potential (OE) test results show that the OE potential of the ternary doped anode prepared in this embodiment can reach 1.54V. The relevant values are summarized in [the table below]. Figure 2 For a comparison of trends, please refer to Figure 5 This potential is 90 mV higher than that of the undoped comparative example 1, which is also higher than the corresponding values of the single-doped and double-doped systems. This can effectively raise the threshold for the occurrence of the oxygen evolution side reaction and ensure that the anode preferentially catalyzes the main reaction of ferrous iron oxidation.
[0043] Figure 3 The data on additive consumption show that the consumption of brightener and leveling agent in this embodiment decreased by 30%. The amount of highly oxidizing intermediates generated in the plating solution decreased as the oxygen evolution side reaction was suppressed, and the degree of oxidative damage to organic additives was significantly reduced, which can maintain the long-term stability of the plating solution performance and reduce the cost of production auxiliary materials.
[0044] Figure 4 In the corresponding durability test, the accelerated hardening life of the sample in this embodiment can reach 675 hours, which is more than 50% higher than that of the undoped comparison. The higher sintering temperature promotes more complete development of the coating crystal phase and further improves the structural integrity. It can effectively prevent corrosive electrolyte from penetrating into the substrate and support the long-term stable operation of the electroplating production line.
[0045] Comparative Example 1 The titanium substrate is made of industrial pure titanium TA2 mesh, roughened by sandblasting with 100-mesh white corundum abrasive at a pressure controlled at 0.5 MPa. The abrasive particles uniformly impact the substrate surface, removing surface machining marks and the original oxide film, forming a rough interface with orderly contours, providing mechanical bonding conditions for coating adhesion. After sandblasting, the titanium substrate is annealed in a muffle furnace for shaping. The furnace temperature is raised to 550℃ and held at that temperature for 1.5 hours, followed by slow cooling with the furnace. This high-temperature treatment eliminates internal residual stress introduced during sandblasting, stabilizes the substrate geometry, and prevents deformation and warping during high-temperature sintering. The annealed substrate is then immersed in a 15% oxalic acid solution for acid etching activation, with the system temperature maintained at 85℃ for 1.5 hours. Under acidic conditions, micro-dissolution occurs on the titanium substrate surface, completely removing the thin oxide layer and forming fine, uniform corrosion pits, further increasing the effective surface contact area. After treatment, the substrate is removed and repeatedly rinsed with deionized water until the surface is neutral. It is then dried in an oven and stored in a dry environment for later use. Two precursor materials, chloroiridium acid and tantalum pentachloride, are weighed according to the set component ratio and added sequentially to anhydrous ethanol solvent. The molar ratio of iridium to tantalum is controlled at 7:3, and the total amount of anhydrous ethanol added is adjusted to ensure a total molar concentration of the two metal elements in the coating solution of 0.25 mol / L. The mixture is continuously magnetically stirred at room temperature for 3 hours, allowing the metal precursors to gradually dissociate and disperse, and the system to gradually transition to a clear and transparent state, forming a uniform and stable coating precursor solution. The prepared coating solution is uniformly brushed onto the pretreated titanium substrate surface. After brushing, it is allowed to stand at room temperature for 5 minutes to allow the coating solution to fully spread and wet the rough interface. Then, it is placed in a 100℃ oven for 5 minutes to allow the ethanol solvent to slowly evaporate, and the solute to uniformly deposit on the substrate surface to form a precursor film.
[0046] After drying, the substrate is transferred to a muffle furnace for pyrolysis sintering, with the temperature increased to 550°C at a rate of 8°C per minute and held at that temperature for 15 minutes. Under high-temperature conditions, the metal precursor undergoes thermal decomposition, gradually transforming into a composite oxide crystalline phase, while simultaneously forming a strong bonding interface with the titanium substrate surface. After each sintering cycle, the substrate is removed and allowed to cool naturally to room temperature, then the coating, drying, and sintering processes are repeated, with the entire cycle repeated 10 times. The layer-by-layer coating structure gradually accumulates thickness with each cycle. The unmodified pure iridium-tantalum system is prone to internal stress concentration during thermal expansion and contraction, creating potential structural defects.
[0047] The titanium substrate, having completed all coating and sintering cycles, was then placed back into a muffle furnace for final heat treatment. The furnace temperature was steadily raised to 550°C and held constant for 1 hour to allow for further growth and refinement of the coating's crystalline phase. After heat treatment, the substrate was slowly cooled to room temperature with the furnace, yielding an undoped reference titanium anode sample.
[0048] The electrochemical performance, service stability, and microstructure of the prepared anode samples were comprehensively characterized, and the test results corresponded to... Figures 2 to 8 .
[0049] The results of the oxygen evolution potential test are summarized in Figure 2 For a comparison of trends, please refer to Figure 5 The oxygen evolution potential of this comparative sample was 1.45V, the lowest among all tested samples. A lower oxygen evolution potential means that oxygen evolution side reactions are more likely to occur, and a large number of highly oxidizing intermediate products will be generated during the anodic operation, which will have a significant negative impact on the plating solution system.
[0050] Figure 3 The data on additive consumption shows that the consumption of brightener and leveling agent in this comparative sample is at the highest level. As a benchmark for the doped system, a large number of strong oxidizing intermediate products continuously oxidize and decompose the organic components in the plating solution, resulting in a fast additive consumption rate and large fluctuations in the performance of the plating solution, requiring frequent replenishment of agents to maintain process stability.
[0051] Figure 4 In the corresponding durability test, the accelerated hardening life of this comparative sample was 440 hours, the shortest among all samples. The short service life is directly related to the structural defects of the coating itself. Corrosive media can quickly erode the substrate through the defect channels, causing coating peeling and anodic failure.
[0052] Microscopic morphology characterization results correspond Figure 7 Under 5,000x magnification, the coating surface is covered with a large number of wide and deep penetrating cracks. The cracks are intersecting and extend directly to the substrate surface. These cracks are products of thermal stress release during pyrolysis sintering, providing a direct channel for electrolyte penetration and are the core structural cause of the short service life of the anode.
[0053] Comparative Example 2 The titanium substrate is made of industrial pure titanium TA2 mesh, which is roughened by sandblasting with 100-mesh white corundum abrasive at a pressure controlled at 0.5 MPa. The abrasive particles uniformly impact the substrate surface, removing surface machining marks and the original oxide film, forming a rough interface with orderly contours, providing mechanical adhesion conditions for coating bonding. After sandblasting, the titanium substrate is placed in a muffle furnace for annealing and shaping. The furnace temperature is raised to 550℃ and held at that temperature for 1.5 hours, followed by slow cooling in the furnace. This high-temperature treatment eliminates internal residual stress introduced during sandblasting, stabilizes the substrate geometry, and prevents deformation and warping during the high-temperature sintering stage.
[0054] After annealing, the substrate is immersed in a 15% oxalic acid solution for acid etching activation. The system temperature is maintained at 85℃ and the immersion time is 1.5 hours. Under acidic conditions, micro-dissolution occurs on the surface of the titanium substrate, the thin oxide layer is completely removed, and fine and uniform corrosion pits are formed, further increasing the effective contact area of the surface. After the treatment is completed, the substrate is taken out and rinsed repeatedly with deionized water until the surface is neutral. It is then placed in an oven to dry and stored in a dry environment for later use.
[0055] Weigh out the three precursor raw materials—iridium chloroacetic acid, tantalum pentachloride, and tin tetrachloride—according to the set component ratios, and add them sequentially to anhydrous ethanol solvent. The molar ratio of iridium to tantalum is controlled at 7:3, and the molar ratio of tin to iridium is controlled at 7:1000. Adjust the total amount of anhydrous ethanol added to achieve a total molar concentration of 0.25 mol / L for the three metal elements in the coating solution. Continuously stir the mixture magnetically at room temperature for 3 hours, allowing the metal precursors to gradually dissociate and disperse, and the system to gradually transition to a clear and transparent state, forming a uniform and stable coating precursor solution. Apply the prepared coating solution evenly to the pretreated titanium substrate surface. After application, allow it to stand at room temperature for 5 minutes to allow the coating solution to fully spread and wet the rough interface. Then, place it in a 100°C oven for 5 minutes to allow the ethanol solvent to slowly evaporate, and the solute to uniformly deposit on the substrate surface to form a precursor film. The dried substrate was transferred to a muffle furnace for pyrolysis sintering, with the temperature increased to 550°C at a rate of 8°C per minute and held at that temperature for 15 minutes. Under high temperature, the metal precursor underwent thermal decomposition, gradually transforming into a composite oxide crystalline phase, while simultaneously forming a strong bonding interface with the titanium substrate surface. After each sintering cycle, the substrate was removed and allowed to cool naturally to room temperature. The coating, drying, and sintering process was repeated 10 times. The layer-by-layer coating structure gradually accumulated thickness with each cycle. Single-element tin doping could, to some extent, regulate the electronic structure of the coating, but its effect on inhibiting thermal stress cracking was relatively limited. The titanium substrate, having completed all coating and sintering cycles, was then returned to the muffle furnace for final heat treatment. The furnace temperature was steadily raised to 550°C and held for 1 hour to further enhance the growth of the coating crystalline phase. After heat treatment, the substrate was slowly cooled to room temperature with the furnace, yielding a tin-doped modified titanium anode sample.
[0056] The electrochemical performance and service stability of the prepared anode samples were characterized, and the test results can be correlated with... Figures 2 to 5 .
[0057] The results of the oxygen evolution potential test are summarized in Figure 2 For a comparison of trends, please refer to Figure 5 The oxygen evolution potential of this comparative sample was 1.49 V, which was 40 mV higher than that of the undoped comparative sample 1. Single-element doping can modulate the electronic configuration of the oxide lattice to some extent and raise the energy barrier of the oxygen evolution reaction, but the modification effect is relatively limited and it still cannot completely suppress the oxygen evolution side reaction under high current density.
[0058] Figure 3 The data on additive consumption show that the consumption of brightener in this comparative sample decreased by 10%, the consumption of leveling agent decreased by 5%, the degree of inhibition of oxygen evolution side reaction was limited, the amount of strong oxidizing intermediate products generated was not significantly reduced, and the effect of reducing additive consumption was not outstanding.
[0059] Figure 4 In the corresponding durability test, the accelerated hardening lifetime of this comparative sample was 530 hours, an improvement of 90 hours compared to Comparative Example 1. Single-element doping has a weak effect on optimizing the microstructure of the coating and cannot effectively fill the microcracks and defects generated during the pyrolysis process. The electrolyte can still slowly erode the substrate along the defect channels, resulting in a limited improvement in anode lifetime.
[0060] Comparative Example 3 The titanium substrate is made of industrial pure titanium TA2 mesh, roughened by sandblasting with 100-mesh white corundum abrasive at a pressure controlled at 0.5 MPa. The abrasive particles uniformly impact the substrate surface, removing surface machining marks and the original oxide film, forming a rough interface with orderly contours, providing mechanical bonding conditions for coating adhesion. After sandblasting, the titanium substrate is annealed in a muffle furnace for shaping. The furnace temperature is raised to 550℃ and held at that temperature for 1.5 hours, followed by slow cooling with the furnace. This high-temperature treatment eliminates internal residual stress introduced during sandblasting, stabilizes the substrate geometry, and prevents deformation and warping during high-temperature sintering. The annealed substrate is then immersed in a 15% oxalic acid solution for acid etching activation, with the system temperature maintained at 85℃ for 1.5 hours. Under acidic conditions, micro-dissolution occurs on the titanium substrate surface, completely removing the thin oxide layer and forming fine, uniform corrosion pits, further increasing the effective surface contact area. After processing, remove the substrate, rinse it repeatedly with deionized water until the surface is neutral, dry it in an oven, and then store it in a dry environment for later use.
[0061] Four precursor materials—iridium chloroacetic acid, tantalum pentachloride, tin tetrachloride, and tetraethyl orthosilicate—weighed according to the set component ratios and added sequentially to anhydrous ethanol solvent. The molar ratio of iridium to tantalum was controlled at 7:3, and the molar ratio of tin to silicon to iridium was controlled at 7:1:1000. The total amount of anhydrous ethanol added was adjusted to achieve a total molar concentration of the four metal elements in the coating solution of 0.25 mol / L. The mixture was continuously magnetically stirred at room temperature for 3 hours. The metal precursors gradually dissociated and dispersed, and the system gradually transitioned to a clear and transparent state, forming a homogeneous and stable coating precursor solution.
[0062] The prepared coating solution was evenly applied to the pretreated titanium substrate surface. After application, the substrate was left to stand at room temperature for 5 minutes to allow the coating solution to fully spread and wet the rough interface. Then, it was placed in a 100°C oven for 5 minutes to allow the ethanol solvent to slowly evaporate and the solute to be evenly deposited on the substrate surface to form a precursor film.
[0063] The dried matrix was then transferred to a muffle furnace for pyrolysis sintering, with the temperature increased to 550°C at a rate of 8°C per minute and held at that temperature for 15 minutes. Under high-temperature conditions, the metal precursor underwent thermal decomposition, gradually transforming into a composite oxide crystalline phase, while simultaneously forming a strong bonding interface with the titanium matrix surface.
[0064] After a single sintering, the substrate is removed and allowed to cool naturally to room temperature. The coating, drying, and sintering processes are repeated, and the entire cycle is repeated 10 times. The layer-by-layer coating structure gradually accumulates thickness with each cycle. The introduction of silicon can fill grain boundary defects, which can alleviate thermal stress cracking to some extent and improve the density of the coating.
[0065] The titanium substrate, having completed all coating and sintering cycles, was then placed back into a muffle furnace for final heat treatment. The furnace temperature was steadily raised to 550°C and held constant for 1 hour to allow for further growth and refinement of the coating's crystalline phase. After heat treatment, the substrate was slowly cooled to room temperature with the furnace, yielding a tin-silicon dual-doped modified titanium anode sample.
[0066] The electrochemical performance, service stability, and microstructure of the prepared anode samples were comprehensively characterized, and the test results corresponded to... Figures 2 to 8 .
[0067] The results of the oxygen evolution potential test are summarized in Figure 2 For a comparison of trends, please refer to Figure 5 The oxygen evolution potential of this comparative sample is 1.51V, which is 20mV higher than that of the tin-doped comparative sample 2. The combination of two elements can play a role in both electronic structure regulation and grain boundary filling, further increasing the oxygen evolution reaction barrier. However, the overall improvement still shows a linear cumulative trend, without a qualitative breakthrough.
[0068] Figure 3 The data on additive consumption shows that the consumption of brightener in this comparative sample decreased by 15%, and the consumption of leveling agent decreased by 10%. With the deepening inhibition of oxygen evolution side reaction, the amount of strong oxidizing intermediate products generated was further reduced, and the additive consumption continued to decrease. However, it still cannot meet the requirements for long-term stable operation under high current density conditions.
[0069] Figure 4In the corresponding durability test, the accelerated hardening life of this comparative sample was 590 hours, which is 60 hours longer than that of comparative sample 2. The filling effect of silicon on the grain boundaries reduced the penetration channels inside the coating, slowed down the corrosion rate of the substrate, and steadily improved the anodic life.
[0070] Microscopic morphology characterization results correspond Figure 8 Under 5,000x magnification, the number of surface cracks in the coating is significantly reduced and the crack width is significantly narrowed. However, there are still minor crack defects in some areas. The dual-doping system can effectively alleviate thermal stress cracking, but it cannot completely eliminate through-hole defects. The electrolyte still has a slow penetration path, which is the structural reason why the anode lifetime cannot achieve a significant leap.
[0071] Combination Figures 2 to 5 The test results show that the anodes of different doping systems exhibit gradient changes in electrochemical selectivity, service durability, and plating solution compatibility. The undoped Comparative Example 1 has the lowest oxygen evolution potential, the highest additive consumption, and the shortest accelerated hardening lifetime, serving as the performance benchmark for the entire test system. The tin-doped Comparative Example 2 shows slight improvements in all indicators, with the oxygen evolution potential increasing by 40 mV compared to the benchmark, the accelerated hardening lifetime extending by 90 h, and additive consumption decreasing simultaneously. The tin-silicon dual-doped Comparative Example 3 achieves further optimization based on the single-doping system, with the oxygen evolution potential increasing by another 20 mV and the accelerated hardening lifetime extending by another 60 h. The performance improvement is basically linearly correlated with the amount of element introduced.
[0072] Examples 1 and 2 employ a tin-silicon-manganese ternary doping system, with core performance enhancements significantly exceeding the linear cumulative law. Example 1 shows a 50mV increase in oxygen evolution potential and a 122-hour increase in accelerated lifetime compared to the dual-doped system, exhibiting the best electrochemical stability. Example 2, due to adjustments in doping ratio and sintering parameters, shows slightly lower oxygen evolution potential and accelerated lifetime than Example 1, but demonstrates better suppression of organic additive consumption. Both types of samples are significantly superior to the dual-doped system overall, with brightener and leveling agent consumption decreasing by a stable 20% to 30%, and the operational stability of the plating bath system is substantially improved.
[0073] Figures 6 to 8 The microscopic morphology characterization provides an intuitive structural explanation for the performance differences. In Comparative Example 1, the coating surface is riddled with wide and deep through-cracks, allowing corrosive electrolyte to directly contact the titanium substrate along these channels, leading to rapid failure. In Comparative Example 3, the number and width of cracks are significantly reduced, but permeable micro-defects still exist, only delaying the corrosion process but not fundamentally blocking it. In the ternary doped examples, the surface cracks in the coating are almost completely eliminated, resulting in a dense and continuous overall structure. The dopant elements work together during pyrolysis, both regulating oxide grain size to alleviate thermal stress and filling grain boundary pores to form a complete barrier layer, structurally cutting off the electrolyte penetration path.
[0074] The three types of doping elements play a role in electronic structure regulation, grain boundary defect filling, and thermal stress mitigation, respectively. They work together to form a synergistic effect, simultaneously improving oxygen evolution selectivity and enhancing structural stability. This modification method does not require increasing the amount of precious metal loading; it can achieve a leap in comprehensive performance with only trace doping. Under the premise of controlling the preparation cost, it can fully adapt to the working conditions of high current density PCB copper electroplating, providing support for cost reduction, efficiency improvement, and long-term stable operation of the production line.
[0075] Based on the comprehensive experimental results, it is clear that this invention achieves a dual leap in catalytic selectivity and structural stability of the iridium-tantalum-based catalytic coating through a preparation process involving micro-doping with tin, silicon, and manganese, combined with multi-layer coating pyrolysis and final heat treatment, without altering the main iridium-tantalum oxide framework. The three doping elements act on multiple dimensions—electronic structure regulation, grain boundary defect filling, and thermal stress mitigation—to produce a synergistic effect. This not only raises the oxygen evolution reaction barrier, guiding the anodic preferential catalysis of ferrous oxide oxidation, but also refines oxide grains, fills microcracks within the coating, and improves overall density and substrate bonding strength. The ternary doped system exhibits significantly better oxygen evolution potential, accelerated lifetime enhancement, and additive loss control than the undoped, single-doped, and dual-doped systems, with performance increases exceeding the linear superposition of the effects of multiple elements, demonstrating non-obvious technical benefits. The entire preparation process follows the industry-standard pyrolysis coating route, requiring no additional specialized equipment. Performance optimization can be achieved with only trace doping at the thousand-level, without increasing the loading ratio of the precious metal iridium. Under the premise of controlling anode manufacturing costs, it can be fully adapted to acidic copper sulfate plating solution systems containing ferrous and ferric redox couples, meeting the high current density and long-term stable operation requirements of PCB electroplating production lines. This provides reliable anode material support for cost reduction, efficiency improvement, and coating quality enhancement in the electroplating process of printed circuit boards.
[0076] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, apparatus, article, or method that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, apparatus, article, or method. Unless otherwise specified, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, apparatus, article, or method that includes that element.
[0077] The above description is only a preferred embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural or procedural transformations made based on the content of the present invention specification and drawings, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.
Claims
1. A method for preparing a ternary doped titanium anode for copper plating on PCBs, characterized in that, Includes the following steps: The titanium substrate was subjected to sandblasting roughening, annealing shaping and acid etching activation treatment in sequence to remove the oxide layer on the surface of the titanium substrate and form a uniform rough interface. After being rinsed with deionized water and dried, it was ready for use. A coating solution was prepared by dissolving chloroiridic acid, tantalum pentachloride, tin tetrachloride, tetraethyl orthosilicate, and manganese nitrate in anhydrous ethanol. The molar ratio of iridium to tantalum was 6–8:2–4. Based on 1000 molar parts of iridium, the molar amounts of tin, silicon, and manganese were 5–10 parts, 1–3 parts, and 0.5–2 parts, respectively. The total molar concentration of iridium, tantalum, tin, silicon, and manganese in the coating solution was 0.2–0.3 mol / L. The coating liquid is applied to the pretreated titanium substrate surface. The amount of coating liquid used per square meter of titanium substrate surface in a single application is 10-20 ml. After drying at 50-100℃ for 5-10 minutes, the temperature is increased to 350-550℃ at a rate of 5-10℃ / min and then sintered at a constant temperature for 15-30 minutes. The application, drying and sintering steps are repeated 8-15 times. The titanium substrate that has undergone repeated brushing and sintering is then subjected to a final heat treatment at 500–600℃ for 1–2 hours to obtain a material suitable for Fe²⁺-containing substrates. + / Fe³ + Insoluble ternary doped titanium anode for copper plating on PCBs using a redox couple system.
2. The method for preparing a ternary doped titanium anode for PCB copper plating according to claim 1, characterized in that, The sandblasting roughening process uses 80-120 mesh white corundum sand, and the sandblasting pressure is 0.4-0.6 MPa.
3. The method for preparing a ternary doped titanium anode for PCB copper plating according to claim 1, characterized in that, The annealing and setting temperature is 500-600℃, and the holding time is 1-2 hours.
4. The method for preparing a ternary doped titanium anode for PCB copper plating according to claim 1, characterized in that, The acid etching activation treatment uses a 10-20% oxalic acid solution, which is soaked at 80-90°C for 1-2 hours.
5. A ternary doped titanium anode for copper plating on PCBs, characterized in that, It is prepared using the preparation method of ternary doped titanium anode for PCB copper electroplating as described in any one of claims 1 to 4.
6. The ternary doped titanium anode for PCB copper plating according to claim 5, characterized in that, The ternary doped titanium anode for PCB copper plating includes: Titanium matrix; An iridium-tantalum-based electrocatalytic active coating is formed on the surface of the titanium substrate, wherein the molar ratio of iridium to tantalum in the iridium-tantalum-based electrocatalytic active coating is 6-8:2-4, and the molar amount of tin is 5-10 parts, the molar amount of silicon is 1-3 parts, and the molar amount of manganese is 0.5-2 parts, based on 1000 parts of iridium. The ternary doped titanium anode is in the Fe²⁺ content + / Fe³ + It is used as an insoluble anode in acidic copper sulfate plating solutions containing redox couples.
7. An application of a ternary doped titanium anode for copper plating on PCBs, characterized in that, The ternary doped titanium anode for PCB copper electroplating as described in claim 5 is applied to Fe²⁺-containing... + / Fe³ + In an acidic copper sulfate plating solution system with a redox couple, it is used as an insoluble anode for copper electroplating.
Citation Information
Patent Citations
Preparation method of titanium anode for PCB electroplating
CN112795974A
Manganese-doped Ir-Ta oxide composite coating titanium anode and preparation method thereof
CN120719327A